Rational Emotive Behaviour Therapy (REBT) dalam Menangani Kecemasan Penderita Ekstrapiramidal Sindrom Mahasiswa UIN Sunan Ampel Surabaya - Faizah, Nurul (Transformatif, 2018)
The focus of this research is to find out how the process and results of Rational Emotive Behaviour Therapy (REBT) to deal with anxiety in patients Extrapyramidal Syndrome student of UIN Sunan Ampel Surabaya. The subjects in this research was a student of the Faculty of Daâwa and Communication UIN Sunan Ampel Surabaya 3rd semester who suffer from anxiety disorders because Extrapyramidal syndrome since the age of 10 years. This research uses qualitative research methods, with a case study and comparative descriptive analysis, the researchers compared before and after the counseling process using Rational Emotive Behaviour Therapy (REBT). The results of this research showed that the process of Rational Emotive Behaviour Therapy (REBT) in dealing with anxiety in patients Extrapyramidal syndrome using three techniques on REBT approaches (techniques disputing irrational belief, rational emotive imagery techniques, and modelling techniques) that do quite successful. It can be seen from the values obtained in the calculation by the standard test with a percentage of 50% - 75% which can be considered quite successful.Keywords: Rational Emotive Behavior therapy, Anxiety